Influence of PEO coatings on mechanical and corrosion properties of Mg-7Y-1Zn alloy. (2020) - Kennedy, Edward; Shivappa,; Sriraman,; Mohan,
Abstract: Magnesium alloys play a vital role in many structural applications due to their lightweight density and high specific strength properties. However, its low corrosion resistance limits its applications. In this study, Plasma electrolytic oxidation (PEO) develop a stable oxide layer on the surface of Mg-7Y-1Zn alloy to enhance the corrosion and mechanical properties. To evaluate the corrosion properties, electro-chemical polarization test was conducted in 3.5% NaCl Solution. The micro-hardness test for mechanical properties of the as-received and PEO coated Mg alloy was done. The results show that corrosion resistance and hardness were significantly increased compared to the base alloy after PEO Coatings due to the formation of the thick oxidation layers.